Hepato-protective and Antioxidant Activity of Extract of Coccania Grandis (Roots) induced by CCl4 in Rats (International Journal of Pharmacy and Life Sciences, 2022)
In the present study an attempt has been made to find out Heptoprotective and Antioxidant Activity of Extract of Coccania Grandis (Roots) Induced By Cc4 In Rats. There are many chemical agents that cause hepatotoxicity and these agents called Hepatotoxins. These cause hepatotoxicity by the generation of free radicals and damage the liver cells and cause of m any liver diseases. Further works are being carried out to isolate and identify the active principle involved in the hepatoprotective and antioxidant activities of this plant extract. The present study has demonstrated that( EECT)(100 and 200 mg/kg) exhibited significant dose-dependent hepatoprotective activity against liver injury induced by CCl4. Carbon tetrachloride induces hepato-toxicity by metabolic activation; therefore, it selectively causes toxicity in liver cells maintaining semi- normal metabolic function. Carbon tetrachloride is metabolically activated by the cytochrome P450 in the endoplasmic reticulum to form a trichloromethyl free radical (ccl3.) which combines with cellular lipids and proteins in the presence of oxygen to induce lipid peroxidation, which leads to change in the structures of endoplasmic reticulum and other membrane, loss of metabolic enzymes activation, reduction of protein synthesis and elevation of serum transaminases leading toliver damage. Amino transferases contribute a group of enzymes that catalyze the interconversion of amino acids and α-ketocids by the transfer of amino group. Carbon tetrachloride is one of the most commonly used hepatotoxins in the experimental study of liver disease. The assessment of liver function can be made by estimating the activities of serum enzymes such as ALT, AST and ALP. During hepatic damage, there may be increase in these enzyme levels in serum with the extent of liver damage. The altered levels of these enzymes in CCl4-treated rats in the present study corresponded to the extensive liver damage induced by the toxin.